Environmental response to the early Toarcian carbon cycle and climate perturbations in the northeastern part of the West Tethys shelf - Ruebsam, W.; Müller, T.; Kovács, J.; Pálfy, J.; Schwark, Lorenz (Elsevier BV, 2018)
Early Toarcian (Early Jurassic; ~183 Ma) climate and carbon cycle perturbations were accompanied by widespread accumulation of bituminous sediments, formed during the Toarcian Oceanic Anoxic Event (T-OAE). On the northwestern Tethyan shelf, organic carbon accumulation was particularly widespread in hydrodynamically restricted regions of the European Epicontinental Basin System (EEBS) where it peaked during the formation of euxinic waters extending into the photic zone. In the adjacent northeastern West Tethys shelf (NE-WTS), an area proximal to the deeper and better ventilated NW Tethys, deposition of strata enriched in organic matter was restricted to depressions of limited spatial extent. While numerous works have addressed the bituminous strata from the EEBS, evolution of environmental conditions and drivers of organic matter accumulation in areas proximal to the open Tethys have received much less attention. Here, we investigated a stratigraphically well-constrained, exceptionally organic matter-rich sediment succession from the NE- WTS deposited during the T-OAE. Organic and isotope geochemical investigations provided insights into the evolution and dynamics of environmental conditions during the T-OAE in a setting proximal to the Tethys. The sedimentary rocks sampled for this study originated from a surface outcrop that experienced weathering-related alteration of its mineral constituents. In particular, sulfides (mainly pyrite) were significantly altered, resulting in a near-quantitative loss of sulfur. In contrast, kerogen as well as bitumen fractions have not been significantly affected by weathering processes and carry a robust paleoenvironmental signal. The new data show that organic carbon accumulation occurred as a direct response to changing environmental conditions that also led to the early Toarcian carbon cycle perturbation. Increase in organic carbon burial occurred in a stepwise manner, following multiple injections of 12 C-enriched carbon into the Earth's ocean-atmosphere system. High algal productivity and the subsequent organic matter decomposition by sulfate reducing bacteria led to an expansion of H 2 S-rich waters into the photic zone, which promoted the growth of Chlorobiaceae. A steady increase in nitrogen isotope values testified to intensified denitrification in an expanded oxygen minimum zone. The resulting decline in the availability of bio-utilizable nitrogen in combination with harsh environmental conditions promoted the proliferation of cyanobacteria as indicated by increasing abundances of 2a-methyl-hopanes. Formation of euxinic waters in the NE-WTS was not associated with a freshwater driven salinity stratification. Organic geochemical salinity indicators (methylated chromanes) attest to normal marine salinity, supporting a strong influence of Tethyan water masses. This study enhances our knowledge on the environmental response towards the early Toarcian climate and carbon cycle perturbations in a setting proximal to the Tethys. We demonstrate that photic zone euxinia was a common and particularly widespread feature of the T-OAE and has not been confined to the hydrodynamically restricted EEBS.